Relationships between upper extremity neuromuscular function and patient-reported outcomes among individuals with a history of glenohumeral labral repair - Katsumi Takeno; Christopher D. Ingersoll; Neal R. Glaviano; Sadik Khuder; Grant E. Norte (PLoS ONE, 2025)
Background Patient-reported outcomes (PROs) are essential components of contemporary healthcare practices, which allow clinicians to effectively monitor clinical outcomes. Objectively measured neuromuscular impairments have been reported among individuals with glenohumeral labral repair, yet their relationship with PROs is unclear. Understanding those relationships would help clinicians explain clinical meaning of such impairments from a patient-oriented perspective. The objective of this study was to determine the relationships between objective metrics of upper extremity neuromuscular function and PROs in individuals with glenohumeral labral repair. Methods 16 individuals with a history of glenohumeral labral repair (13 males/3 females, age: 24.1 ± 5.5 years, time from surgery: 36.3 ± 33.3 months) volunteered. Neuromuscular functions, characterized by shoulder abduction and wrist flexion maximal voluntary isometric contraction (MVIC) torque, Hoffmann reflex (spinal pathway), and active motor threshold (AMT, corticospinal pathway) of the upper extremity muscles, were assessed bilaterally. Pain, physical activity level, Disability of Arm, Shoulder and Hand (DASH) questionnaire, Oxford Shoulder Score (OSS), and Veteran’s Rand 12-Item Health Survey (VR-12) were used to quantify self-reported upper extremity function and global health, encompassing both mental and physical components. Bivariate correlations and multiple linear regression were used to identify the variance explained by neuromuscular outcomes in each PRO. Results Involved limb wrist flexion MVIC torque moderately correlated with DASH ( r = −.523, p = .045). AMT of middle deltoid moderately correlated with OSS (ρ = .570, p = .021). Age and current activity level explained 73.2% variance in the VR-12 physical component (adjusted R 2 = .732, p < .001). Age moderately correlated with the VR-12 mental component (ρ = .550, p = .027). Conclusions Greater involved limb wrist flexor strength, corticospinal excitability of the middle deltoid, as well as greater age and lesser activity level explained better perceived function and health. These results support the clinical relevance of muscle strength and neural function to patient recovery from glenohumeral labral repair.